2015
DOI: 10.1097/mpg.0000000000000553
|View full text |Cite
|
Sign up to set email alerts
|

Novel Risk Factors for Recurrent Clostridium difficile Infection in Children

Abstract: Objectives Clostridium difficile, a common cause of antibiotic-associated diarrhea, has been reported to recur in high rates in adults. The rates and risk factors for recurrent Clostridium difficile infection (rCDI) in children have not been well established. Methods We conducted a retrospective cohort study of 186 pediatric patients seen at a tertiary care referral center over a 5-year period diagnosed with a primary infection with Clostridium difficile. Children with recurrent disease, defined as return of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 31 publications
2
69
2
3
Order By: Relevance
“…Recurrence of CDI can occur in 20-30% after initial infection, with the frequency of recurrence rising further after subsequent infections (19)(20)(21). Risk factors for recurrent CDI in children include IBD (22,23), malignancy, recent surgery, and the number of antibiotic exposures by class (19).…”
Section: Fmt For Recurrent CDI In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Recurrence of CDI can occur in 20-30% after initial infection, with the frequency of recurrence rising further after subsequent infections (19)(20)(21). Risk factors for recurrent CDI in children include IBD (22,23), malignancy, recent surgery, and the number of antibiotic exposures by class (19).…”
Section: Fmt For Recurrent CDI In Childrenmentioning
confidence: 99%
“…Recurrence of CDI can occur in 20-30% after initial infection, with the frequency of recurrence rising further after subsequent infections (19)(20)(21). Risk factors for recurrent CDI in children include IBD (22,23), malignancy, recent surgery, and the number of antibiotic exposures by class (19). FMT has been shown to be more effective than antibiotics for recurrent CDI in adults (12,13); van Nood et al (12) showed a cure rate of 81% after FMT compared with 31% with vancomycin alone and Cammarota et al (13) had similar results with resolution of CDI in 90% of those treated with FMT compared with 26% treated with vancomycin.…”
Section: Fmt For Recurrent CDI In Childrenmentioning
confidence: 99%
“…Caution needs to be used to interpret the results in patients between 1 and 3 years of age and additional agents of infection need to be investigated (35). Nonetheless, in patients with risk factors and in special pediatric populations such as those with IBD and immunosuppressed patients (17,18), prompt and sensitive identification of C. difficile is necessary to allow appropriate treatment, prevent transmission, and improve outcomes.…”
Section: Difficile Diagnostic Testsmentioning
confidence: 99%
“…Therefore, the differences in the performance characteristics of the various methodologies for the detection of CDI in children in these high-risk populations were not assessed. In a separate study assessing risk factors for children with recurring CDI, malignancy, recent surgery, and antibiotic exposure were the most significant factors (18). Both enzyme immunoassays (EIAs) and nucleic acid amplification tests (NAATs) were used as laboratory tests for the detection of C. difficile; however, no data on the differences in test performance were presented.…”
mentioning
confidence: 99%
“…Other risk factors include the presence of an ileal pouch [52], fecal incontinence, and concomitant antacid use and hypoalbuminemia [47,[53][54][55]. For pediatric cases, recent evidence from Nicholson and colleagues showed that among 186 pediatric patients, malignancy (OR 3.39, 95 % CI 1.52-7.85), recent surgery (OR 2.40; 95 % CI 1.05-5.52), and the number of antibiotic exposures by class (OR 1.33, 95 % CI 1.01-1.75) were significantly associated with recurrent CDI [56]. Two of the above risk factors, PPIs and appendectomy, are explored in more detail below.…”
Section: Recurrent C Difficile Infection (Rcdi)mentioning
confidence: 99%